Examining the effects of self-regulated learning-based teacher feedback on English-as-a-foreign-language learners’ self-regulated writing strategies and writing performance - Yang, Li Francoise; Liu, Yanhong; Xu, Zhiqing (Frontiers in Psychology, 2022)
The current study examines the effect of teacher feedback on fostering self-regulated English-as-a-foreign-language(EFL) writers. Adopting aquasi-experimental design, this study was conducted among seventy students from two parallelintact English writing classes at the tertiary level. While conventional feedback at the level of task was used in the control group, feedback at the level of process and self-regulation with supplementary activities was adopted for the treatment group. This SRL-based feedback intervention lasted one semester. Students took a pre-test, an immediate and a delayed post-test to measure their improvement in English writing performance, as well as their use of writing strategies for self-regulated learning(SRL), with a questionnaire. The results reveal that the SRL-based feedback intervention had a positive impact on EFL student writers’ writing performance as well as their reported use of SRL writing strategies. While the analytic writing scores for the subcategories of organisation, vocabulary and content significantly increased overtime for the treatment group, there was little change in languageuse. ANCOVA analyses suggest significantly positive results for the treatment group in the improvement of SRL writing strategies with goal-oriented monitoring, knowledge rehearsal, feedback handling, and interest enhancement, and the intervention also developed the use of SRL strategies for text processing, idea planning, motivational self-talk, and emotional control.